Stationary Points—I: One-Dimensional p-Fuzzy Dynamical Systems. (28th September 2013) - Silva, Joao de Deus M.; Leite, Jefferson; Bassanezi, Rodney C.; Cecconello, Moiseis S.
Abstract : p-Fuzzy dynamical systems are variational systems whose dynamic is obtained by means of a Mamdani type fuzzy rule-based system. In this paper, we will show the 1-dimensional p-fuzzy dynamical systems and will present theorems that establish conditions of existence and uniqueness of stationary points. Besides the obtained analytical results, we will present examples that illustrate and confirm the obtained mathematical results.